2013
DOI: 10.4172/2329-8901.1000101
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics: Mechanisms of Action and Clinical Applications

Abstract: Probiotics are living microorganisms which when taken in adequate amount provides benefit to the host. While this beneficial effect was originally thought to stem from improvements in the intestinal microbial balance, there is now substantial evidence that probiotics can also provide benefits by modulating immune functions. Extrapolation of immunomodulatory effects found in the laboratory and in animal studies with outcomes in human trials presents a difficult challenge. Not all probiotics are created equal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 146 publications
0
33
0
1
Order By: Relevance
“…This figure also outlines possible mechanisms of probiotics action in skin, female urogenital tract, and respiratory tract. It includes modulation of the systemic immune function, competitive exclusion of harmful microorganisms, production of antimicrobial substances and growth substrates, inhibition of bacterial toxin production, among others (Bermudez-Brito et al 2012;Gogineni et al 2013;Markowiak and Śliżewska 2017;Rahmati Roudsari et al 2013).…”
Section: Potential Mechanisms Of Probiotics Actionmentioning
confidence: 99%
“…This figure also outlines possible mechanisms of probiotics action in skin, female urogenital tract, and respiratory tract. It includes modulation of the systemic immune function, competitive exclusion of harmful microorganisms, production of antimicrobial substances and growth substrates, inhibition of bacterial toxin production, among others (Bermudez-Brito et al 2012;Gogineni et al 2013;Markowiak and Śliżewska 2017;Rahmati Roudsari et al 2013).…”
Section: Potential Mechanisms Of Probiotics Actionmentioning
confidence: 99%
“…It plays an important role in cell-to-cell signaling mechanism, which helps in the regulating traits of enteric microbes, and allows them to colonize as well as infect the host successfully. A study reported that L. acidophillus secretes molecule that inhibits the quorum sensing or interaction with E. coli O 157:H7, as a result bacterial toxicity is restricted [83].…”
Section: Quorum Signallingmentioning
confidence: 99%
“…The health benefits of consuming probiotics are frequently mentioned in the scientific literature [2][3][4][5][6]. One of the most frequently described qualities associated with probiotics is their effectiveness at preventing skin, oral, respiratory, gastrointestinal, and urogenital tract infections (reviewed in [7,8]).…”
Section: Introductionmentioning
confidence: 99%